Needs Analysis in Preparing Playing Technique Skills Tests for Adolescent Football Athletes - Himawan Wismanadi; Achmad Widodo; Afif Rusdiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to develop a test for football-playing techniques for teenagers aged 16-20. The process involves analyzing technical skills components, conducting expert focus group discussions (FGD), developing test types, conducting first and second trials, and analyzing the results. The first trial involved 30 players and a bivariate correlation test, followed by 75 players and factor analysis. The results will be used to determine priority techniques for developing youth football technique test instruments. The research aims to improve football skills among teenagers. The result of factor analysis showed variables LLP2 (0.814), RSho2, (0.178), LSho2 (.683) on the first factor, while the variables RLP2(0.557), CP2(0.776) on the second factor. Conclusion: Left long passing (LLP), proper shooting (RSho), and left shooting (LSho) are the priority, while right long passage (RLP) and control passing are the second priority.